Dynamic behaviors of CO2 bubbles coalescing at two parallel capillary orifices in microalgae suspension. (November 2015) - Zhao, Sha; Ding, Yu-Dong; Chen, Rong; Liao, Qiang; Zhu, Xun
Highlights: Coalescence behaviors of CO2 bubbles in microalgae suspension were studied. Many microalgae enriched at the interface hindered the coalescence of bubbles. Bubbles grew slowly and were easily detached in microalgae suspension. A critical gas flow rate of 15 mL/min was obtained for coalesced bubble detachment. Abstract: In the microalgae cultivation process, CO2 in the bubble form is supplied into photobioreactors as carbon source for microalgae growth. The coalescence of CO2 bubbles greatly affects the mass transport and thus the biomass production rate. In this work, therefore, the dynamic behaviors of CO2 bubbles coalescing at two parallel capillary orifices in microalgae suspension were visually studied and compared with pure water. The movement and distribution of microalgae at gas–liquid interface were also observed. The effects of the center distance of capillary orifices and gas flow rate were also analyzed. It was found that many microalgae and microalgae aggregation adsorbed on the surface of the bubble and tended to distribute between the two bubbles when two bubbles coalesced. Besides, it was also found that in microalgae suspension more time was needed for the coalescence of bubbles, and the coalesced bubbles were more easily detached as a result of low surface tension but with lower terminal velocity after detachment than that in pure water. When the center distance of capillary orifices was 1.5 mm ( S  = 3 d 0 ), the coalesced bubbles had less growth time and smaller detachment diameter. A critical gas flow rate of 15 mL/min was obtained, at which the minimum detachment diameter and terminal velocity of coalesced bubble was achieved. These findings will be beneficial for the design of aeration system of photobioreactors for microalgae cultivation to enhance the mass transport at the interface.